. Subtract the Second polynomial from first. 8x2 – 2x + 12 ; 6x2 + 2x -7
Answers
Answered by
0
Answer:
Explanation:
Given:
y
=
−
2
x
3
−
6
x
2
+
8
x
+
24
Note that the ratio of the first and second terms is the same as that of the third and fourth terms. So this cubic will factor by grouping. We can first separate out the common factor
−
2
rather than tidying it up later...
y
=
−
2
x
3
−
6
x
2
+
8
x
+
24
y
=
−
2
(
x
3
+
3
x
2
−
4
x
−
12
)
y
=
−
2
(
(
x
3
+
3
x
2
)
−
(
4
x
+
12
)
)
y
=
−
2
(
x
2
(
x
+
3
)
−
4
(
x
+
3
)
)
y
=
−
2
(
x
2
−
4
)
(
x
+
3
)
y
=
−
2
(
x
2
−
2
2
)
(
x
+
3
)
y
=
−
2
(
x
−
2
)
(
x
+
2
)
(
x
+
3
)
Answer link
Step-by-step explanation:
hope you like make me brain list
Similar questions